Pizzaro - Hernandez, Simon (Columbia : La Popular Productions, 2016)
Exiled in Barcelona, Maria Pizzaro, daughter of Colombian guerrilla commander Carlos Pizarro Leongomez, receives a letter from her father who was killed after signing a peace deal with the Columbian government. Maria returns to her homeland and undertakes a personal journey to understand the events that led her father to his death.
Verzio Film Festival Submission.
Verzio Film Festival Submission
Keywords: Documentary films